Sensory quality characteristics of catfish fermented sausage (Pangasius sp.) with the addition of biostarter from fermented sausages - Leksono, Tjipto; Sinulingga, Elsa Apriana Br.; Sidauruk, Santhy Wisuda (Universitas Malikussaleh, 2025)
Fermented sausages are processed meat products made through a fermentation process with or without the help of bacterial starter cultures. The source of microorganisms in making fermented sausages can be sourced from natural microorganisms in meat (spontaneous fermentation), or by adding a starter culture (controlled fermentation). The purpose of this study is to find out the level of consumer acceptance of catfish fermented sausages made with the addition of biostarters from fermented sausages. The method used in this study is an experiment, namely conducting experiments on making catfish fermented sausages with different biostarter concentrations (0%, 0.2%, 0.4% and 0.6%) which are fermented within 0 days, 3 days, 6 days and 9 days. The results of the study showed that the best catfish fermented sausage with the addition of biostarter was with 04% treatment. The appearance value is 7.52 (brilliant color, attractive reddish-brown color). Aroma value 7.73 (strong smoking, fermentation and spice aroma) Taste value 8.03 (good taste, typical acidity of fermented products, not fishy). Texture value 7.62 (compact, dense and elastic). Based on this value, catfish fermented sausage with the addition of biostarter is still accepted by consumers with a fairly good quality characteristic value. Keywords: Biostarter; Catfish; Fermented Sausages; Sensory Quality